The design of sites : patterns for creating winning web sites - Van Duyne, Douglas K., 1966- (Prentice Hall, 2007)
"The Design of Sites, Second Edition, is the definitive reference for the principles, patterns, methodologies, and best practices underlying exceptional Web design. If you are involved in the creation of dynamic Web sites, this book will give you all the necessary tools and techniques to create effortless end-user Web experiences, improve customer satisfaction, and achieve a balanced approach to Web design."--Jacket